Approach to Mediastinal Fine Needle Aspiration Cytology. (18th November 2022) - Li, Zaibo; Xu, Huihong; Fan, Fang
Abstract : Mediastinal fine needle aspirations are routinely encountered in cytopathology practice. Mediastinal lesions may pose diagnostic challenges owing to their rarity and locations associated with the complexity of the mediastinal anatomic structures in the thoracic cavity. Diagnosing mediastinal lesions and guiding patient management usually require correlating with clinical and radiologic findings, being familiar with cytomorphologic features and appropriately triaging the diagnostic material for ancillary testing. This review proposes a practical approach to interpret mediastinal fine needle aspirations and emphasizes potential diagnostic pitfalls for mediastinal lesions including benign cysts, thymic neoplasms, lymphoproliferative disorders, germ cell tumors, mesenchymal tumors, and metastatic tumors.